(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: Lymph nodes, a component of the lymphatic system are tiny bean-shaped organs. They are variable in number but are constantly found in certain body regions such as the neck, axilla, mediastinum, abdomen, and groin. Many histological changes, like the depletion of germinal centers, and the degree of fibrosis and lipomatosis secondary to the aging process were the main points to be focused on in this study. Recently some clinical procedures like intranodal vaccination, lymph node transplantation, and transfer have demonstrated the need for an accurate knowledge of these degenerative processes. Objectives: To identify and differentiate the age-related and region-related changes of the histoarchitecture of lymph nodes. Study Design: A Cross-Sectional study Place and Duration of Study: The study was conducted at Peshawar Medical College, in collaboration with the Forensic Lab of Khyber Medical College, Peshawar from Jan 2021 to Jun 2021. Methods: The current study is a cross-sectional study. Which involved 30 autopsies of 3 different age groups. Each group consists of 10 cases. Lymph nodes from different body regions (cervical, axillary, mesenteric, and inguinal regions) were obtained. The deceased adults, who ranged from 15 to 65+ years of age, were included in this study. To evaluate and standardize the degree of degeneration, a scoring system was applied, and the changes were scored as 0 (no change), 1 (mild to moderate change), and 2 (marked change). Data analysis was done using statistical software to compute the prevalence and pattern or variation analysis. Results: The research examined lymph node modifications in three age groups. The average age of the participants was 55.42 years (±10.20). The proportion of fibrosis was age-dependent and demonstrated higher frequencies in older ages. The prevalence of lipomatosis rose rapidly with age, affecting a few younger people, and increased significantly by a p-value of 0.0023. Young individuals had more rampant germinal centers with a marked decline in older ones. The depletion of germinal centers was higher with aging (p=0.0351, suggesting that there is an age-associated drop in lymph node efficiency). Conclusion: This study gives us knowledge of some non-pathological changes of lymph nodes with advancing age, and the reason for diminished or weak immunological response to infection and cancer metastasis in the elderly.